Association Between Semiology and Anatomo-functional Localization in Patients With Cingulate Epilepsy: A Cohort Study. (31st May 2022) - Pelliccia, Veronica; Avanzini, Pietro; Rizzi, Michele; Caruana, Fausto; Tassi, Laura; Francione, Stefano; Gozzo, Francesca; Mariani, Valeria; d'Orio, Piergiorgio; Castana, Laura; Mai, Roberto; Terzaghi, Michele; et al.
Abstract : Background and Objectives: Cingulate epilepsy (CE) is a rare type of focal epilepsy that is challenging to diagnose because of the polymorphic semiology of the seizures, mimicking other types of epilepsy, and the limited utility of scalp EEG. Methods: We selected consecutive patients with drug-resistant CE who were seizure-free after surgery, with seizure onset zone (SOZ) confirmed in the cingulate cortex (CC) by histology or stereo EEG. We analyzed subjective and objective ictal manifestations using video recordings and correlated semiology with anatomical CC subregion (anterior, anterior middle, posterior middle, and posterior) localization of SOZ. Results: We analyzed 122 seizures in 57 patients. Seizures were globally characterized by complex behaviors, typically natural seeming and often accompanied by emotional components. All objective ictal variables considered (pronation of the body or arising from a lying/sitting position, tonic/dystonic posturing, hand movements, asymmetry, vocalizations, fluidity and repetitiveness of motor manifestations, awareness, and emotional and autonomic components) were differently distributed among CC subregions ( p < 0.05). Along the rostro-caudal axis, fluidity and repetitiveness of movement, vocalizations, body pronation, and emotional components decreased anterior–posteriorly, whereas tonic/dystonic postures, signs of lateralization, and awareness increased. Vestibular and asymmetric somatosensory, somatosensory, and epigastric and enteroceptive/autonomic symptoms were distributed differently among CC subregions ( p < 0.05). Along the rostro-caudal axis, vestibular, somatosensory, and somatosensory asymmetric symptoms increased anterior–posteriorly. Discussion: CE is characterized by a spectrum of semiologic manifestations with a topographic distribution. CE semiology could indicate which cingulate sector is primarily involved.